Development control in Sabah within a context of planning system in Malaysia - Ahmad Sarkawi, Azila; Mohamed Osman, Mariana; Bachok, Syahriah; Rabe, Noor Suzilawati (2011)
Development control is a legal procedure that has provided local authorities with the jurisdiction responsibility to translate ideas and policies of town and country planning into reality. It is also a process which consists of both the making of development plans and the practice of development control by local planning authorities. The processes included preparing and implement that plan through development plans, granting or refusing planning permission in their areas. In general, this research studies the development control system in Sabah in general and specific focus is given on the planning application and planning approval process. The research analyses the current practice of development control in the state, the factors influencing local authority’s decision making process as well issues and problems faced by the current implementation of planning application process. The methods used to collect the data were interview surveys, content analysis, semi-structured questionnaire survey and focus groups discussion. The results of the survey were further analyzed by conducting cross-tabulation, chi-square and also spearman tests. The research found that the planning application and approval process of all local authorities in Sabah are quite similar among themselves. However, there are some differences in the administration procedure depending on the needs of the authority and locality. The study also found that the current planning application and planning approval process in the state of Sabah was similar to planning application and planning approval process in Peninsular Malaysia